Protective Effect of Renin-Angiotensin System Inhibitors on Parkinson’s Disease: A Nationwide Cohort Study - Jo, Youngkwon; Kim, Seungyeon; Ye, Byoung Seok; Lee, Euni; Yu, Yun Mi (Frontiers in Pharmacology, 2022)
Background: Renin-angiotensin system (RAS) inhibitors have been suggested as protective agents in Parkinson’s disease (PD). However, epidemiological evidence on the association between RAS inhibitors and the development of PD is inconsistent. Objectives: To investigate the effect of RAS inhibitors on PD risk in patients with ischemic heart disease (IHD) by type and cumulative duration of RAS inhibitors and their degree of blood-brain barrier (BBB) penetration ability. Methods: This was a propensity score-matched retrospective cohort study using 2008–2019 healthcare claims data from the Korean Health Insurance Review and Assessment database. The association between RAS inhibitor use and PD in patients with IHD was evaluated using multivariate Cox proportional hazard regression analysis. The risks are presented as adjusted hazard ratios (aHRs) and 95% confidence intervals (CIs). Results: Over a 10-year follow-up, 1,086 of 62,228 IHD patients developed PD. The Cox regression model showed that the use of RAS inhibitors was significantly associated with a lower risk of PD (aHR = 0.75; 95% CI 0.66–0.85) than the non-use of RAS inhibitors. Specifically, this reduced risk of PD only remained with the use of BBB-crossing angiotensin II receptor blockers (ARBs) (aHR = 0.62; 95% CI = 0.53–0.74), and this association was more definite with an increasing cumulative duration. A significantly reduced risk of PD was not observed with the use of BBB-crossing angiotensin-converting enzyme inhibitors. Conclusions: The use of ARBs with BBB-penetrating properties and a high cumulative duration significantly reduces the risk of PD in IHD patients. This protective effect could provide insight into disease-modifying drug candidates for PD.